Internalization of Islamic Values in Facing the Threat of Drugs in Adolescents in Kalibaru, Cilincing - Hidayat, Rahmat; Lismawati, Lismawati (Raudhah Publisher, 2024)
In the face of this threat, an effective strategy to form a strong adolescent character and prevent them from the influence of drugs is to internalize Islamic values. This study aims to evaluate the role of internalization of Islamic values in dealing with the threat of drug abuse in adolescents and how this approach can be implemented in prevention efforts. The results of the study show that the internalization of Islamic values in adolescents can help strengthen moral awareness in them. Religious education has a significant role in this internalization process, by teaching Islamic values that encourage adolescents to distance themselves from drug use. Prevention of drug abuse in adolescents through the internalization of Islamic values also requires cooperation between families, schools, and the community. In conclusion, the application of Islamic values internally has a significant role in overcoming the threat of drug abuse to adolescents. This study makes a significant contribution to efforts to prevent drug abuse in adolescents with a holistic approach and Islamic values as the moral basis.